162k views
2 votes
How do you solve the equation |x^2-x+1|=3

User Rohan Veer
by
5.5k points

1 Answer

3 votes

Explanation:

Given


|x^2-x+1|=3


\mathrm{Apply\:absolute\:rule}:\quad \mathrm{If}\:|u|\:=\:a,\:a>0\:\mathrm{then}\:u\:=\:a\:\quad \mathrm{or}\quad \:u\:=\:-a


x^2-x+1=-3\quad \mathrm{or}\quad \:x^2-x+1=3

solving


x^2-x+1=-3


x^2-x+1+3=-3+3


x^2-x+4=0


\mathrm{Discriminant\:}\:x^2-x+4=0


\mathrm{For\:a\:quadratic\:equation\:of\:the\:form\:}ax^2+bx+c=0\mathrm{\:the\:discriminant\:is\:}b^2-4ac


\mathrm{For\:}\quad a=1,\:b=-1,\:c=4\quad


b^2-4ac=\left(-1\right)^2-4\cdot \:\:1\cdot \:\:4

= 1 - 16

= -15


\mathrm{Discriminant\:\:cannot\:be\:negative\:for\:}x\in \mathbb{R}


\mathrm{The\:solution\:is}


\mathrm{No\:Solution\:for}\:x\in \mathbb{R}

similarly solving


x^2-x+1=3


x^2-x+1-3=3-3


x^2-x-2=0


\mathrm{Solve\:with\:the\:quadratic\:formula}


\mathrm{For\:a\:quadratic\:equation\:of\:the\:form\:}ax^2+bx+c=0\mathrm{\:the\:solutions\:are\:}


x_(1,\:2)=(-b\pm √(b^2-4ac))/(2a)


\mathrm{For\:}\quad a=1,\:b=-1,\:c=-2:\quad x_(1,\:2)=(-\left(-1\right)\pm √(\left(-1\right)^2-4\cdot \:1\left(-2\right)))/(2\cdot \:1)


x=(-\left(-1\right)+√(\left(-1\right)^2-4\cdot \:1\left(-2\right)))/(2\cdot \:1)=2


x=(-\left(-1\right)-√(\left(-1\right)^2-4\cdot \:1\left(-2\right)))/(2\cdot \:1)= -1


\mathrm{The\:solutions\:to\:the\:quadratic\:equation\:are:}


x=2,\:x=-1

so


\mathrm{Combine\:Solutions:}


\mathrm{No\:Solution}\quad \mathrm{or}\quad \left(x=-1\quad \mathrm{or}\quad \:x=2\right)


x=-1\quad \mathrm{or}\quad \:x=2

User Hunterjrj
by
4.8k points